2020
DOI: 10.1038/s41467-020-15620-2
|View full text |Cite
|
Sign up to set email alerts
|

Long-term isolation of European steppe outposts boosts the biome’s conservation value

Abstract: The European steppes and their biota have been hypothesized to be either young remnants of the Pleistocene steppe belt or, alternatively, to represent relicts of long-term persisting populations; both scenarios directly bear on nature conservation priorities. Here, we evaluate the conservation value of threatened disjunct steppic grassland habitats in Europe in the context of the Eurasian steppe biome. We use genomic data and ecological niche modelling to assess pre-defined, biome-specific criteria for three p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
79
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(83 citation statements)
references
References 63 publications
2
79
0
Order By: Relevance
“…Palynological studies have evidenced that extensive areas of the Mediterranean region were vegetated by steppe‐like formations during glacial periods that became progressively replaced by temperate forests during interglacial stages (Carrión et al., 2012; Sánchez‐Goñi et al., 1999). Consequently, the confinement of the saltmarsh band‐winged grasshopper in refuges of suitable habitat during unfavourable periods may have led to processes of allopatric divergence along the Quaternary as reported for steppe‐like and halophytic species presenting similar environmental requirements (Kajtoch et al., 2016; Kirschner et al., 2020). Demographic inferences based on genomic data contrast with the predictions of our ENM, which suggests that the extent of climatically suitable habitats for the species have tended to increase since the LGM (Figure 1f).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Palynological studies have evidenced that extensive areas of the Mediterranean region were vegetated by steppe‐like formations during glacial periods that became progressively replaced by temperate forests during interglacial stages (Carrión et al., 2012; Sánchez‐Goñi et al., 1999). Consequently, the confinement of the saltmarsh band‐winged grasshopper in refuges of suitable habitat during unfavourable periods may have led to processes of allopatric divergence along the Quaternary as reported for steppe‐like and halophytic species presenting similar environmental requirements (Kajtoch et al., 2016; Kirschner et al., 2020). Demographic inferences based on genomic data contrast with the predictions of our ENM, which suggests that the extent of climatically suitable habitats for the species have tended to increase since the LGM (Figure 1f).…”
Section: Discussionmentioning
confidence: 99%
“…According to this hypothesis, disjunctions arose by colonization events and subsequent isolation processes linked to Quaternary climate oscillations (Kadereit & Yaprak, 2008). Sea‐level drawdown (∼125 m; Litcher et al., 2010) and expansions of steppe‐like environments (Kajtoch et al., 2016; Kirschner et al., 2020) during Pleistocene glacial periods might have facilitated the dispersal of steppe species across seaways and favourable habitats and, ultimately, led to the colonization of geographically distant regions that have remained isolated since then (Ortiz et al., 2007). For example, the Strait of Gibraltar, where the distance between the Iberian Peninsula and Africa shortened to a few kilometers during the Pleistocene coldest stages, which might have favoured the exchange of fauna and flora between the two continents (Graciá et al., 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The sampled species are all typical elements of the Eurasian steppe biome, and represent different reproductive, life-history, and dispersal strategies. Collecting permits are given in Kirschner et al 19.…”
Section: Samplingmentioning
confidence: 99%
“…Population grouping into two clusters, corresponding to extrazonal and zonal lineages, was the optimal solution for all investigated species based on Bayesian population assignment (Figure 2A). Though Kirschner et al 19 found further subgrouping within these clusters, the focus of our study are the contrasting demographic dynamics between extrazonal and zonal steppe lineages, so we constrained all analyses to the clusters at the highest hierarchical level, that is, K=2 for all species. Numbers of individuals and loci analysed are given in Supplementary Table 1.…”
Section: Clustering Analysesmentioning
confidence: 99%
“…In Central Europe, the remains of the more or less continuous Pleistocene Artemisia -Chenopodiaceae cold steppe (tundra-steppe) belt 1 , 5 can be found nowadays only in azonal steppe islands and in artificial, man-made steppe-like habitats 11 , 12 . In recent years, steppe plants and their shared history with the Eurasian steppe belt have come under the focus of much research 13 21 .…”
Section: Introductionmentioning
confidence: 99%